Full-band Monte Carlo simulation of high-energy carrier transport in single photon avalanche diodes with multiplication layers made of InP, InAlAs, and GaAs - Dolgos, Denis; Meier, Hektor; Schenk, Andreas; Witzigmann, Bernd (Journal of Applied Physics, 2012)
We investigate the high-energy charge dynamics of electrons and holes in the multiplication process of single photon avalanche diodes. The technologically important multiplication layer materials InP and In 0.52Al 0.48As, used in near infrared photon detectors, are analyzed and compared with GaAs. We use the full-band Monte Carlo technique to solve the Boltzmann transport equation which improves the state-of-the-art treatment of high-field carrier transport in the multiplication process. As a result of the computationally efficient treatment of the scattering rates and the parallel central processing unit power of modern computer clusters, the full-band Monte Carlo calculation of the breakdown characteristics has become feasible. The breakdown probability features a steeper rise versus the reverse bias for smaller multiplication layer widths for InP, In 0.52Al 0.48As, and GaAs. Both the time to avalanche breakdown and jitter decrease with shrinking size of the multiplication region for the three examined III-V semiconductors. © 2012 American Institute of Physics.
CRIS-Team Scopus Importer:2021-06-11